2005
DOI: 10.1111/j.1442-2042.2005.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinephric angiomyolipoma: A unique development pattern surrounding the kidney

Abstract: We report a case of a 31-year-old man with extrarenal angiomyolipoma of the perinephric space. He presented with asymptomatic macrohematuria. Computed tomography of the abdomen revealed a large perinephric mass which was separated from the right kidney and its unique growth appeared to have surrounded the kidney. Extrarenal angiomyolipomas of the perinephric fat are rare and they should be considered in the differential diagnosis of a retroperitoneal mass where asymptomatic macrohematuria was presented at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Renal AMLs account for 1% of renal lesions, occurring more commonly in women [2] with an overall incidence in the general population of 0.07–0.3% [25]. Renal AMLs are sometimes referred to as hamartomas (a benign tumor-like growth composed of typical cells and tissues found in the area of the body where it occurs, but growing in a nonorganized fashion) or choristomas (a mass of normal tissue found in an ectopic location).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal AMLs account for 1% of renal lesions, occurring more commonly in women [2] with an overall incidence in the general population of 0.07–0.3% [25]. Renal AMLs are sometimes referred to as hamartomas (a benign tumor-like growth composed of typical cells and tissues found in the area of the body where it occurs, but growing in a nonorganized fashion) or choristomas (a mass of normal tissue found in an ectopic location).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of perivascular epithelioid cells (PEC) is often used to characterize angiomyolipomas since these cells show immunoreactivity for muscle markers (epithelial membrane antigen, keratin, vimentin, desmin, and actin) and HMB-45 [29]. Positive immunoreactivity for HMB-45, a monoclonal antibody raised against a melanoma-associated antigen, is characteristic of AMLs and can be used to differentiate AMLs from other similar appearing lesions such as liposarcomas, lipomas, leiomyosarcomas or, leiomyomas [20, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a unifying histogenetic theory, angiomyolipomas are now considered within the category of neoplasms consisting of perivascular epithelioid cells (so-called PEComas) (60). Perirenal involvement usually results from perinephric extension of an angiomyolipoma of the kidney; primary perirenal angiomyolipoma arising from the perinephric mesenchyme is extremely rare (61). Primary perirenal angiomyolipomas have a strong female predilection and, like sporadic renal angiomyolipomas, are associated with an increased risk of hemorrhage.…”
Section: Liposarcomamentioning
confidence: 99%
“…Obara et al [ 17 ] in 2005 reported a 31-year-old man who presented with painless visible haematuria. He had a CT scan of abdomen which revealed a large perinephric mass in his right kidney without any evidence of contrast enhancement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Minja et al [ 18 ] stated that presence of perivascular epithelioid cells (PEC) tends often to be used to characterize angiomyolipomas in view of the fact that these cells exhibit immunoreactivity for muscle markers (epithelial membrane antigen, keratin, vimentin, desmin, and actin) and HMB-45 [ 68 ]. It has been stated that positive immunoreactivity for HM-45, a monoclonal antibody which has been raised against melanoma-associated antigen, is characteristic of angiomyolipomas (AMLs) and it can be used to differentiate angiomyolipomas (AMLs) from other similar appearing lesions, for example, liposarcomas, lipomas, leiomyosarcomas, or leiomyomas [ 11 , 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%